EFEKTIVITAS PENGGUNAAN DANA DESA PADA PROGRAM PEMBERDAYAAN MASYARAKAT DI DESA KANAWONG KECAMATAN SIAU BARAT KABUPATEN KEPULAUAN SIAU TAGULANDANG BIARO TAHUN ANGGARAN 2017 - SANDALA, FASCAL MAREL; RORONG, ARIE JUNUS; LONDA, VERY (JURNAL ADMINISTRASI PUBLIK, 2018)
This research aim to find out the effectiveness of the use of the village Fund program community empowerment didesa Kanawong on fiscal year 2017. Research methods used in this research is qualitative. The data used are composed of primary data and secondary data. With the technique of collecting data through observation, interview and documentation, data obtained from various sources and analyzed with data reduction steps, the presentation of the data and the withdrawal of the conclusion. Results of the study showed that the use of the funds in the village of Kanawong sub-district of the Western Islands Regency Siau SITARO program effectiveness to achieve the empowerment of communities in the measure of the transparency of both the program less efektiv village Government does not explain about the use of the village Fund, on aspects of participation is already running on the community through involvement in activities of the integrated service post, while on the Government less look real on the training program the village chief and the posyandu activities, device already running and can be enjoyed by society, in contrast to training activities yet can be enjoyed. Posyandu program can be completely accountable, but less on the training can be accounted for. Empowerment program on training does not continue the Government’s work plan is seen from the village of the year 2018, posyandu empowerment as well as the budget continues to increase. The conclusions and suggestions of transparency on the activities of the training of village chief and devices as well as the activities of posyandu in village Kanawong less effective, participation is already a real run on the society, training activities the village chief and the village has yet to be be enjoyed while at posyandu activities can be enjoyed, the less training activities can be accountable, the activities of posyandu can be accountable. Training activities do not continue, while the community empowerment Program for the empowerment of posyandu continues. Keywords : effectiveness, Village Fund, Empowerment